SISTEM INFORMASI AGENDA SURAT PADA PENGADILAN NEGERI BANTUL - , HERMINIDA F A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bantul District Court is government instance which one of its activites including processing data of letter that came in and out between instances. The process of data management letter which is not computerized yet, allows for neither late disposition letter nor data loss. Based on these problems, has to be built a system which can handle process management letter data and report letter. This letter agenda information is built web-based using PHP as the language program, assisted by framework CodeIgniter, Javascript with framework JQuery, Web server Apache, and MySQL for database management. This system has integrated modules such as paper management, data management, and report management. Data management manages the reference data that will be used by paper management and will show the output of the report and available in the report management module.